Objective truth as the purpose of proving (Journal of actual problems of jurisprudence, 2018)
The article considers the objective truth as an objective proof. Achieving goals is as consistent decision of the investigating authorities, the prosecutor and the courts of a number of interconnected sub-objectives on the way to proving goal – achieving the truth. Objective truth in this sphere of social life is the highest form of subjective reflection of objective reality, there is a complete and exact match of subjective judgments investigated the facts and circumstances. Key words: truth, proof, objective truth, epistemology, the court, the prosecutor, inquiry, investigation.